Frictional heat-assisted performance enhancement in dynamic Schottky contact of Al/Ag2Se-based tribovoltaic nanogenerator - Supakarn Worathat; Utchawadee Pharino; Phakkhananan Pakawanit; Arunothai Rattanachata; Rangson Muanghlua; Sugato Hajra; Hoe Joon Kim; Saichon Sriphan; Naratip Vittayakorn (Journal of Materiomics)
The tribovoltaic nanogenerator (TVNG) has evolved in recent years as a novel type of nanogenerator designed to address the limitations of the standard triboelectric nanogenerator in terms of output signal and charge generation. Besides the outstanding characteristics, the tribovoltaic effect can also well be coupled with another effect to further boost the output performance. In this work, we proposed firstly a frictional heat-assisted performance enhancement in dynamic Schottky contact from the rubbing between n-type silver selenide (Ag2Se) and aluminum. The chemical composition and physical characteristics of the Ag2Se ceramic were analyzed using X-ray diffraction, scanning electron microscopy, and Synchrotron X-ray tomography techniques. UV–Vis spectroscopy and UPS were also utilized in order to validate the semiconducting property of the n-type Ag2Se ceramic. Moreover, the presence of the Schottky junction was demonstrated through the analysis of the current-bias voltage characteristic curve of the Ag2Se/aluminum (Al) contact under varying stress and temperature conditions. The built-in electric field plays a crucial part in the tribovoltaic effect by efficiently transferring the excited carriers to an external load through sliding contact between Ag2Se and Al. Demonstrating the synergy between tribovoltaic and thermoelectric effects becomes achievable through the excellent thermoelectric property of Ag2Se. Herein, the proposed TVNG generated a peak output voltage and current of around 0.7 V and 24.8 nA, respectively, achieving a maximum output power of 12.6 nW at a load resistance of 10 kΩ. The influence of frictional heat on the output performance of the proposed TVNG was well demonstrated by the thermal-induced voltage and enhanced electrical output from continuous sliding. The concepts given in this study establish the basis for the progress of effective energy collection employing semiconducting materials and the advancement of flexible harvesting and sensing device development in the future.